2002
DOI: 10.1023/a:1016344030772
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The HOMO energies and the charges on the aromatic carbons of two sets of MAO-A-inhibiting phenylisopropylamines, one containing 4-amino substituents, were calculated by the AM1 method, in order to evaluate the importance of charge-transfer interactions between drug and enzyme. Multiple-linear regressions of the pIC50 values on the calculated descriptors were performed with 33 compounds from the two sets, and separately with each set. A poor correlation was obtained when the two sets were merged, as a result of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 13 publications
0
9
0
2
Order By: Relevance
“…Accordingly, a handful of QSAR studies have shown that electronic features of the benzene ring (e.g. CHELPG atomic charges, HOMO energies) are the most important factors to determine the affinity of AMPH derivatives for MAO-A, and hence that their variation caused by substituents can greatly modulate their potency as enzyme inhibitors (Norinder et al, 1994;Vallejos et al, 2002;Fresqui et al, 2013). In this respect, the presence of a single substituent with electron-donor properties (e.g.…”
Section: Aromatic Ring Substitutionmentioning
confidence: 99%
“…Accordingly, a handful of QSAR studies have shown that electronic features of the benzene ring (e.g. CHELPG atomic charges, HOMO energies) are the most important factors to determine the affinity of AMPH derivatives for MAO-A, and hence that their variation caused by substituents can greatly modulate their potency as enzyme inhibitors (Norinder et al, 1994;Vallejos et al, 2002;Fresqui et al, 2013). In this respect, the presence of a single substituent with electron-donor properties (e.g.…”
Section: Aromatic Ring Substitutionmentioning
confidence: 99%
“…9-11 Structure-activity relationship (SAR) studies, including quantitative analyses (QSAR), [10][11][12] have shown that the presence of electron-donating, unbranched, alkylthio substituents at the para position of the aromatic ring of the amphetamine scaffold generate potent and selective MAO-A inhibitors. In addition, a few studies have shown that the (S)-isomers of substituted amphetamines (which are always dextrorotatory) are the eutomers.…”
Section: Introductionmentioning
confidence: 99%
“…3, structure 4) [96]. All molecules were optimized geometrically and HOMO energies and charges on the aromatic carbons were calculated using AM1 method [97].…”
Section: Prediction Of Mao Activity Through 3d Ligand-based Modelsmentioning
confidence: 99%